Understanding Saving Decisions in Digital Banking Among Generation Z: The Role of Financial Literacy and Trust - Made Ayu Desy Geriadi; Putu Lidia Marini (JUSTBEST Journal of Sustainable Business and Management, 2026)
The rapid development of digital banking has significantly transformed financial behavior, particularly among Generation Z consumers. Despite the increasing adoption of digital banking services, concerns regarding security, privacy, and reliability remain important factors influencing saving decisions in digital banking platforms. This study aims to analyze the effect of financial literacy on saving decisions in digital banking through trust as a mediating variable among Generation Z consumers. This study employed a quantitative research approach using a survey method involving 200 Generation Z respondents who actively used digital banking services in Indonesia. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that financial literacy positively and significantly affects trust and saving decisions in digital banking. Furthermore, trust positively and significantly affects saving decisions and successfully mediates the relationship between financial literacy and saving decisions. The results imply that financially literate individuals tend to possess stronger confidence toward digital banking systems, which subsequently encourages positive saving behavior. This study contributes to the development of Behavioral Finance Theory by explaining the cognitive and psychological mechanisms underlying digital saving behavior among Generation Z consumers. Practically, the findings provide implications for digital banking institutions regarding the importance of financial education, cybersecurity enhancement, and trust-building strategies in encouraging sustainable saving behavior among young consumers.